Enhanced Physicochemical and Biological Properties of Ion-Implanted Titanium Using Electron Cyclotron Resonance Ion Sources - Hegedűs, Csaba (Materials (Basel), 2016)
The surface properties of metallic implants play an important role in their clinical success. Improving upon the inherent shortcomings of Ti implants, such as poor bioactivity, is imperative for achieving clinical use. In this study, we have developed a Ti implant modified with Ca or dual Ca + Si ions on the surface using an electron cyclotron resonance ion source (ECRIS). The physicochemical and biological properties of ion-implanted Ti surfaces were analyzed using various analytical techniques, such as surface analyses, potentiodynamic polarization and cell culture. Experimental results indicated that a rough morphology was observed on the Ti substrate surface modified by ECRIS plasma ions. The in vitro electrochemical measurement results also indicated that the Ca + Si ion-implanted surface had a more beneficial and desired behavior than the pristine Ti substrate. Compared to the pristine Ti substrate, all ion-implanted samples had a lower hemolysis ratio. MG63 cells cultured on the high Ca and dual Ca + Si ion-implanted surfaces revealed significantly greater cell viability in comparison to the pristine Ti substrate. In conclusion, surface modification by electron cyclotron resonance Ca and Si ion sources could be an effective method for Ti implants.